1983
DOI: 10.1055/s-2007-1018805
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Aldosterone Response to Furosemide Test in Patients with Shy-Drager Syndrome

Abstract: We examined the renin-angiotensin-aldosterone system in seven patients with Shy-Drager syndrome by studying their response to the stimulation of 1 mg/kg furosemide injection followed by sitting for 1 hour. Six of the seven patients showed a low response of plasma renin activity to the stimulation. However, in five of the low responders, the plasma aldosterone levels after stimulation were observed to be similar to those of the control subjects; in addition, an increment in the plasma cortisol level appeared al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1987
1987

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Khoner et al (1971) found no changes in serum FFA concentrations in hypertensive patients treated over a period of 1 year with frusemide. Similarly there is no evidence that frusemide affects plasma cortisol concentrations in either normal or hypertensive subjects (Fraser et al, 1965;Tosti-Croce et al, 1981;Sasaki et al, 1983).…”
Section: Critique Ofstudymentioning
confidence: 99%
“…Khoner et al (1971) found no changes in serum FFA concentrations in hypertensive patients treated over a period of 1 year with frusemide. Similarly there is no evidence that frusemide affects plasma cortisol concentrations in either normal or hypertensive subjects (Fraser et al, 1965;Tosti-Croce et al, 1981;Sasaki et al, 1983).…”
Section: Critique Ofstudymentioning
confidence: 99%